Peripheral global neglect in high vs. low autistic tendency - Crewther, Daniel P.; Crewther, David P. (Frontiers in Psychology, 2014)
In addition to its core social deficits, autism is characterised by altered visual perception, with a preference for local percept in those high in autistic tendency. Here, the balance of global versus local percepts for the perceptually rivalrous diamond illusion was assessed between groups scoring high and low on the Autism Spectrum Quotient (AQ). The global percept of a diamond shape oscillating horizontally behind three occluders can as easily be interpreted as the local percept of four line elements, each moving vertically. Increasing the luminance contrast of the occluders with respect to background resulted in an increase of initial global percept in both groups, with no difference in sensitivity between groups. Presenting the target further into the periphery resulted in a marked increase in the percentage of global perception with visual field eccentricity. However, while the performance for centrally presented diamond targets was not different between AQ groups, the peripheral global performance of the High AQ group was significantly reduced compared with the Low AQ group. On the basis of other imaging studies, this peripheral but not foveal global perceptual neglect may indicate an abnormal interaction between striate cortex and the Lateral Occipital Complex, or to differences in the deployment of attention between the two groups.